IGCP Project: Precambrian in Mobile Zones -Meetings in 1974 - Brucker, W.; Anderson, M. (Geoscience Canada, 1975)
Summary During 1973 an International Union of Geological Sciences (IUGS) correlation project dealing with the Precambrian of mobile zones east and west of the North Atlantic began to operate; excursions were conducted in Morocco (1973) and northwestern France ( 1974), and a meeting was held in Paris in January 1974 to discuss problems associated with correlating the areas of Precambrian included. In April 1974. it became a key project of the International Geological Correlation Programme (IGCP), and the Board of IGCP suggested that it take in a similar project (Precambrian Stratigraphy) proposed by the Geological Survey of India. At a constitutional meeting in Paris, November 1974, the organization of the modified project and the rules governing it (statutes) were set up, and a limited programme of future activities agreed upon pending the holding of the first plenary session in Moscow in September 1975 This paper is a brief report of the two Paris meetings and of the scope of the project at the present time.